Two ligand-binding sites in the O2-sensing signal transducer HemAT: implications for ligand recognition/discrimination and signaling - Pinakoulaki, Eftychia; Yoshimura, Hideaki; Yoshioka, Shiro; Aono, Shigetoshi; Varotsis, Constantinos; Daskalakis, Vangelis; Pinakoulaki, Eftychia (My University, 2006)
We have identified a ligand (CO) accommodation cavity in the signal transducer sensor protein HemAT (heme-based aerotactic transducer) that allows us to gain single-molecule insights into the mechanism of gas sensor proteins. Specific mutations that are distal and proximal to the heme were designed to perturb the electrostatic field near the ligand that is bound to the heme and near the accommodated ligand in the cavity. We report the detection of a second site in heme proteins in which the exogenous ligand is accommodated in an internal cavity. The conformational gate that directs the ligand-migration pathway from the distal to the proximal site of the heme, where the ligand is trapped, has been identified. The data provide evidence that the heme pocket is the specific ligand trap and suggest that the regulatory mechanism may be tackled starting from more than one position in the protein. Based on the results, we propose a dynamic coupling between the two distinct binding sites as the underlying allosteric mechanism for gas recognition/discrimination that triggers a conformational switch for signaling by the oxygen sensor protein HemAT
Keywords: Fourier transform infrared spectroscopy; Heme; Oxygen; Binding sites (Biochemistry); Electric fields; Photochemistry; Gas